An analysis of selected grade 11 learners' interactions with geometry tasks using visualization processes: a case study in Namibia - Kabuku, Brian S (Rhodes University, Faculty of Education, Department of Education, 2017)
This case study was conducted at a secondary school where I teach, situated in the semi-rural setting of Bukalo village in Namibia, and sought to gain insights into the nature and role of visualisation processes employed when selected grade 11 learners interacted with selected geometry problems. According to Mariotti and Pensci (1994), visualisation takes place when "thinking is spontaneously accompanied and supported by images" , and helps students to understand the problem at hand. Visualisation is regarded as "making the unseen visible and imagery as the power to imagine the possible and the impossible" (Mason 1992). The study is located within an interpretive research paradigm in order to obtain in-depth understanding of the participants' visualisation processes. Within this paradigm, both quantitative and qualitative approaches were adopted. The eight Grade 11 participants engaged with 12 items of the Geometry Visualisation Tasks (GVT) worksheets. Data was collected using video-recorded learners' interactions with the GVT, observations, stimulated recall interviews and post-GVT interviews with the learners. During the data analysis stage, I used inductive analysis to determine patterns evident in learners 'thinking processes'. My analytical framework consisted of indicators that were used to identify and classify visualisation processes for each task of the GVT for each participant. I adapted this framework from Ho (2010) and Ho, Ramful and Lowrie's (2015) clarification of the representations. The findings from this study revealed that the use of visualisations facilitated meaningful learning when learners made use of these to develop and scaffold their conceptual understanding. The findings revealed that most learners used visualisation processes fairly to very accurately when solving geometry problems. They used visualisation processes by using sketches and diagrams that transformed a mathematical problem pictorially, connected their thinking to previous knowledge and experience, clarified the algebraic task and assisted them to understand the spatial relationships within each task.
Keywords: Mathematics -- Study and teaching -- Activity programs; Geometry -- Study and teaching (Secondary) -- Namibia; Geometry -- Study and teaching (Secondary) -- Namibia -- Cast studies; Visualization